Smlednik Castle - Štular, Benjamin (E-Monographiae Instituti Archaeologici Sloveniae, 2015)
Modern science started studying the Smlednik Castle over a century and a half ago. However, what might be even more important is the fact that more or less intense conservation works have been carried out at this location for over half a century. Regardless of this there is almost no expert literature on the castle to be found: short papers can be counted on the fingers of one hand, while monograph publications are sought in vain. The situation regarding contributions that promotes cultural heritage is somewhat better. The purpose of the book in front of you is thus clear: to present the history of the research and conservation efforts as well as the findings gained from the latest research in one book.This is the English translation of the original publication in Slovenian Grad Smlednik. Raziskave 2011-2012 published in 2013 as the second issue of the series Monografije CPA. The translation differs from the original in two ways. First, it omits the appendices. Secondly, a chapter on 3D scanning of the Smlednik Castle in 2007 including interactive 3D model is added.